Penentuan Transmisivitas dan Porositas Efektif Untuk Mengkaji Proses Gerakan Airtanah Pada Lahan Heterogen - Mahmud Achmad; Sigit Supadmo Arif (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1997)
The main purpose of this research is to determine properties of non-homogeneous ill-drained area which are reflected by transmissivity and effective porosity. The flow of water was analyzed using Darcy law and Boussinesq equations which were developed based on analogy theory of heat conduction to 2-Dimension (pseudo 3-D) of transient water flow. Based on the formula, transmissivity and effective porosity have been determined through mathematical model. The model needs daily deep water table as the main data. The model was tested in PG Jatitujuh Cirebon. The transmissivity and effective porosity information were very useful to solving drainage problems in the ill-drained area. Result of iteration method indicated that the land have 11 and S are 0,070 - 0,698 rnlm and 0,10 - 91,0 m2/day respectively. A R-square test was used to compare deep water table between observation data and output model each of bore hole, and was found average R-square is 0,8519 and standard of error is 0,0981.